Gynaecologists' perceptions of outpatient gynaecologic and obstetric care in Germany during the COVID-19 pandemic - Carsten Hagenbeck; Johannes Soff; Laura Mause; Jan Hoffmann; Tim Ohnhäuser; Arno Stöcker; Janine Zöllkau; Nadine Scholten (BMC, 2023)
Abstract The measures taken to contain the COVID-19 pandemic had a major impact on society, affecting medical care as well as the utilization of medical services. We aimed to identify pandemic-related changes in gynaecologic/obstetric care through the personal experience of practitioners in the outpatient sector in Germany. Three consecutive anonymous online surveys of practising gynaecologists were conducted during the pandemic (07-09/2020, 11-12/2020 and 09-11/2021). Appointment management, medical supply and patients' demand as well as concomitant circumstances were queried. Data from 860 (393, 262 and 205 from the first, second and third surveys, respectively) respondents were analysed. At the peak of the first COVID-19 wave, more than 50% of the gynaecologists surveyed had cancelled cancer screening appointments. There was a significant association between fear of self-infection and cancellation of cancer screening appointments (p = 0.006). An increase in domestic violence was reported by 13%, an increase in obesity by 67% and more advanced tumours due to delayed screening by 24% of respondents. Primary gynaecological oncological prevention was reduced in supply and demand during the COVID-19 pandemic, and this shortfall should be addressed in future similar situations. Prenatal care has been offered continuously since the start of the pandemic in Germany.